Changes in Functional Glucocorticoid Sensitivity of Isolated Splenocytes Induced by Chronic Psychosocial Stress – A Time Course Study - Kempter, Elena; Amoroso, Mattia; Duffner, Hannah L.; Werner, Andrea M.; Langgartner, Dominik; Kupfer, Sandra; Reber, Stefan O. (Frontiers in Immunology, 2021)
Chronic psychosocial stress is a risk factor for the development of numerous disorders, of which most are associated with chronic low-grade inflammation. Given the immunosuppressive effects of glucocorticoids (GC), one underlying mechanism might be the development of stress-induced GC resistance in certain immune cell subpopulations. In line with this hypothesis, male mice exposed to the chronic subordinate colony housing (CSC, 19 days) model develop GC resistance of in vitro lipopolysaccharide (LPS)-stimulated splenocytes, splenomegaly and an increased percentage of splenic CD11b+ cells. Here male C57BL/6N mice were euthanized at different days during CSC, and following 30 days of single housing after stressor termination to assess when CSC-induced splenic GC resistance starts to develop and whether this is a transient effect. Moreover, splenic CD11b, GC receptor (GR) and/or macrophage migration inhibiting factor (MIF) protein levels were quantified at respective days. While mild forms of CSC-induced GC resistance, increased splenic CD11b expression and/or splenomegaly were detectable on days 8 and 9 of CSC, more severe forms took until days 15 and 16 to develop, but normalized almost completely within 30 days following stressor termination (day 51). In contrast, splenic GR expression was decreased in CSC versus single-housed control (SHC) mice at all days assessed. While MIF expression was increased on days 15 and 16 of CSC, it was decreased in CSC versus SHC mice on day 20 despite persisting splenomegaly, increased CD11b expression and functional GC resistance. In summary, our data indicate that GC resistance and CD11b+ cell-mediated splenomegaly develop gradually and in parallel over time during CSC exposure and are transient in nature. Moreover, while we can exclude that CSC-induced reduction in splenic GR expression is sufficient to induce functional GC resistance, the role of MIF in CD11b+ cell-mediated splenomegaly and GC resistance requires further investigation.